Investigation and Evaluation of the Transdermal Delivery of Ibuprofen in Various Characterized Nano-Drug Delivery Systems - Jeanri Myburgh; Wilna Liebenberg; Clarissa Willers; Admire Dube; Minja Gerber (Pharmaceutics, 2023)
The aim was to assess the suitability of three nano-based transdermal drug delivery systems containing ibuprofen: a nano-emulsion, a nano-emulgel, and a colloidal suspension with ibuprofen-loaded nanoparticles. Understanding the transdermal delivery of ibuprofen using nano-based drug delivery systems can lead to more effective pain relief and improved patient compliance. Characterization tests assessed the suitability of the developed drug delivery systems. Membrane release and skin diffusion studies, along with tape stripping, were performed to determine drug release and skin permeation of ibuprofen. In vitro cytotoxicity studies on HaCaT cells were conducted using MTT and neutral red assays to evaluate the safety of the developed drug delivery systems. Characterization studies confirmed stable drug delivery systems with ideal properties for transdermal delivery. Membrane release studies demonstrated the successful release of ibuprofen. In vitro skin diffusion experiments and tape stripping, detecting ibuprofen in the receptor phase, stratum corneum-epidermis, and epidermis-dermis, indicating successful transdermal and topical delivery. The in vitro cytotoxicity studies observed only minor cytotoxic effects on HaCaT cells, indicating the safety of the developed drug delivery systems. The investigation demonstrated promising results for the transdermal delivery of ibuprofen using the developed drug delivery systems, which contributes to valuable insights that may lead to improved pain management strategies.